Pengembangan Kerupuk Ceker Ayam Berbasis Limbah Rumah Potong Ayam dengan Cost-Benefit Analysis untuk Meningkatkan Nilai Jual Ekonomi - Fahlevi, Dini Syahriza; Ahmad, Safriza Naufal Amzad (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
The waste from chicken feet is often overlooked and discarded, especially in the Banda Aceh area, due to low demand. This research aims to assess the economic feasibility of processing chicken feet waste into crackers using a Cost-Benefit Analysis approach. Data collection was conducted through interviews with chicken slaughterhouse owners and literature studies on the waste processing process and micro-business analysis. A quantitative approach was used by estimating fixed costs, variable costs, revenues, and simulating scenarios of changes in cost assumptions and selling prices. The results indicate that this business has a Benefit-Cost Ratio  (BCR) of 1.94, indicating economic feasibility. Sensitivity simulations show that the business remains profitable even if the selling price of crackers drops to Rp200,000/kg (BCR: 1.55) or if raw material costs increase by 10% (BCR: 1.84). With a total annual net profit reaching Rp18,160,000, this business has the potential to enhance the added value of previously worthless livestock waste. This study concludes that processing chicken feet waste into crackers is an economical solution that also supports sustainable waste management. The findings can serve as a reference for business actors and policymakers to develop waste-based innovations. Further research could focus on product diversification based on waste and business risk analysis. Keywords: Cost-Benefit Analysis, Chicken Foot Chips, Slaughterhouses